Verb Agreement In Kalati Brahui - Zahid Ali; Shazia Moula Bakhsh; Muhammad Shoaib Khan; Najamuddin Sohu; Muhammad Idrees Shar (Kurdish Studies, 2023)
Brahui is one of the most ancient languages on earth. It belongs to Dravidian family. The current research work attempts to analyze the Agreement of verb order in intransitive and in intransitive verbs in Brahui, mainly focusing on the Kalati Brahui. The study analyses the Kalati Brahui verbs to see their agreement with subject, object, person, number, aspect, tense, mood, etc. The research is descriptive, analytical, and qualitative in nature. The data have been collected by the researchers via unstructured interview of native participants from Kalat district. The participants have been selected conveniently. The data have been analyzed with the perspective of ‘Agreement Rules’ by Dense Brey "The Brahui Language Part I" (1909). Towards the end, it is seen that Kalati Brahui verb shows agreement with various constituents in sentences. The results show these agreements: subject-verb agreement, object-verb agreement, number, person, aspect, and tense agreement.